Eficiência e ciclo de vida das cooperativas de crédito: uma abordagem econômica e social - Letícia Luanda Maia (2022)
Financial institutions have an important role in financial intermediation between savers and borrowers. As a type of financial institution, credit unions differentials are the social aspect. They are organizations formed by individuals seeking common interesting. It began because of market failure, and they generate benefits for its members beyond financial proposes (such as service delivery, job and income generation). For this social benefit, economic efficiency is also important. However, two aspects need attention. First, the efficiency analyzes of credit unions commonly focus strictly on economic aspects. Few studies consider social efficiency. Second, the number of credit unions in Brazil have to fall and possible it emphasis economic rather social aspects over the life cycle. In this context, I aim to analyze the behavior of the economic and social efficiencies of credit unions throughout the life cycle. I analyzed Brazilian credit unions will be in the period from 2016 to 2020. To determine the economic and social efficiencies used the Data Envelopment Analysis (DEA) with Variable Returns of Scale (VRS) model product orientated. The variables (inputs and outputs) were raised in the literature. To identify the life cycle, I proposed a life cycle model to credit unions based on McKillop (1997, 2000), Cook (1995) and Cook and Burress (2009), one of the main contributions of this thesis. The proposed model considers the phases: (i) nascent, (ii) transition, (iii) mature, (iv) decline and (v) decision. The phases were identified by Cluster Analysis. To confront economic and social efficiencies with the life cycle, I adopted descriptive analysis and median test. Cooperatives show greater economic efficiency in the Mature (MD) stages and a decrease in the last Decline and Decision (DD) stage. As for social efficiency, there is a reduction in social efficiency in the Transition and Growth (TC) stages, followed by an increase in the final stage (DD). Thus, in the Decline and Decision (DD) stage there is a prioritization of social aspects in relation to economic ones, which can lead to noncontinuity of the organization. The result reinforces that economic efficiency is necessary to maintain the activity of cooperatives in performing their social role.